2018
DOI: 10.1186/s13014-018-1202-z
|View full text |Cite
|
Sign up to set email alerts
|

Progression of hearing loss after LINAC-based stereotactic radiotherapy for vestibular schwannoma is associated with cochlear dose, not with pre-treatment hearing level

Abstract: BackgroundAlthough stereotactic radiotherapy (SRT) for vestibular schwannoma has demonstrated excellent local control rates, hearing deterioration is often reported after treatment. We therefore wished to assess the change in hearing loss after SRT and to determine which patient, tumor and treatment-related factors influence deterioration.MethodsWe retrospectively analyzed progression of hearing loss in patients with vestibular schwannoma who had received stereotactic radiosurgery (SRS) or fractionated stereot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…48 This time lag created by using an arbitrary cut-off can deceptively associate pre-treatment PTA or GRC with the hearing outcome, especially if the follow-up period is not long enough. Linge et al 49 demonstrated this problem in their study, which analysed the hearing outcome in three different ways: functional hearing loss, loss of baseline GRC, and PTA increase per month. The pretreatment PTA and V90 of the cochlea were associated with hearing outcomes if the endpoint was functional hearing loss (GRC I and II) or loss of baseline GRC.…”
Section: Hearing Outcome Assessmentmentioning
confidence: 99%
“…48 This time lag created by using an arbitrary cut-off can deceptively associate pre-treatment PTA or GRC with the hearing outcome, especially if the follow-up period is not long enough. Linge et al 49 demonstrated this problem in their study, which analysed the hearing outcome in three different ways: functional hearing loss, loss of baseline GRC, and PTA increase per month. The pretreatment PTA and V90 of the cochlea were associated with hearing outcomes if the endpoint was functional hearing loss (GRC I and II) or loss of baseline GRC.…”
Section: Hearing Outcome Assessmentmentioning
confidence: 99%
“…Most reports included patients with shorter follow-up which may affect accurate assessment of tumor control and underestimate long-term sequelae. Hearing loss is dynamic over time and ideally assessed with minimum of 2-year follow-up, although longer follow-up may demonstrate further increase rate of hearing loss [29,44]. Statistics were overall well described but limited.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…As the organs and tissues at risk include the cochlea, the vestibular organ, and the brainstem, reducing radiation dose is relevant. The risk of hearing loss after radiotherapy seems to be dependent on the dose administered to the cochlea, therefore a reduction of cochlear irradiation may result in better long-term hearing [22][23][24][25][26][27][28][29]. The consequences of low-dose brain irradiation are not well understood; however, it is possible that even small amounts of radiation have an impact on the healthy brain tissue [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…When hearing preservation is of patient’s utmost importance, radiation therapy with low dose to the cochlea should be considered. 20 - 22 However, whether this hearing preservation will be maintained in the long run is questionable as hearing clearly decreases after ten years of follow-up. 23 - 25 This decline is suggested to result from direct cochlear nerve compression by the tumor in the internal acoustic canal resulting in impedance of the auditory nerve.…”
Section: Discussionmentioning
confidence: 99%